The upstream components of the Wnt signalling pathway in the dynamic EMT and MET associated with colorectal cancer progression - Vincan, Elizabeth; Barker, N. (Springer Netherlands, 2008)
The constitutive activation of ß-catenin-dependent ('canonical') Wnt signalling is a necessary initiating event in the genesis of most colorectal cancers. As this constitutive activation occurs through genetic mutation of one of the down-stream components of the signalling pathway, it was presumed that additional regulation of ß-catenin-dependent Wnt signalling would be inconsequential. However, it is now recognised that additional modulation of ß-catenin-dependent Wnt signalling is involved in tumour progression, and many of the genes associated with tumour invasion and metastasis are ß-catenin/TCF transcriptional target genes that are dynamically regulated during cancer progression. Intriguingly, the demonstration that naturally occurring inhibitors of Wnt-Frizzled (FZD) interaction are bona fide tumour suppressors in this cancer suggests that additional modulation of Wnt signalling is via the upstream components of the pathway. This is corroborated by recent studies that demonstrate tumour-promoting roles for Wnt and FZD per se. Moreover, both ß-catenin-dependent and ß-catenin-independent Wnt/FZD-mediated signalling is implicated during the dynamic and reversible EMT and MET that underscore colorectal cancer progression. Importantly, therapeutic targeting of the Wnt signalling pathway at the plasma membrane is clearly indicated by the profound anti-tumour activity of small molecule inhibitors and dominant-negative receptor constructs that target the receptor complex. The potential to effectively target EMT and MET processes at the plasma membrane via the upstream components of the Wnt signalling pathway offers new hope for anti-cancer therapy. © 2008 Springer Science+Business Media B.V.